Republic of Congo : Staff Report-Press Release; Staff Report; Debt Sustainability Analysis, and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Republic of Congo's Review Under the Extended Credit Facility (ECF). The Republic of Congo's ECF program supports the authorities' efforts to restore fiscal sustainability and rebuild regional reserves while improving governance and protecting vulnerable groups. The Congolese authorities have stepped up efforts in 2018 and 2019 to address the economic crisis and the associated governance challenges. The ECF-supported program aims to help the Republic of Congo restore macroeconomic stability, including debt sustainability, and lay the foundations for higher and more inclusive growth. It also seeks to improve governance to achieve greater efficiency and transparency in the management of public resources, especially in the oil sector. The Fund-supported program is expected to contribute positively to the regional strategy and stability efforts of the Central African Economic and Monetary Union. The report also highlights that it is key to promote the productivity of factor inputs by increasing investments in human capital.